Genome Size Reduction and Transposon Activity Impact tRNA Gene Diversity While Ensuring Translational Stability in Birds. (3rd February 2021) - Ottenburghs, Jente; Geng, Keyi; Suh, Alexander; Kutter, Claudia
Abstract: As a highly diverse vertebrate class, bird species have adapted to various ecological systems. How this phenotypic diversity can be explained genetically is intensively debated and is likely grounded in differences in the genome content. Larger and more complex genomes could allow for greater genetic regulation that results in more phenotypic variety. Surprisingly, avian genomes are much smaller compared to other vertebrates but contain as many protein-coding genes as other vertebrates. This supports the notion that the phenotypic diversity is largely determined by selection on non-coding gene sequences. Transfer RNAs (tRNAs) represent a group of non-coding genes. However, the characteristics of tRNA genes across bird genomes have remained largely unexplored. Here, we exhaustively investigated the evolution and functional consequences of these crucial translational regulators within bird species and across vertebrates. Our dense sampling of 55 avian genomes representing each bird order revealed an average of 169 tRNA genes with at least 31% being actively used. Unlike other vertebrates, avian tRNA genes are reduced in number and complexity but are still in line with vertebrate wobble pairing strategies and mutation-driven codon usage. Our detailed phylogenetic analyses further uncovered that new tRNA genes can emerge through multiplication by transposable elements. Together, this study provides the first comprehensive avian and cross-vertebrate tRNA gene analyses and demonstrates that tRNA gene evolution is flexible albeit constrained within functional boundaries of general mechanisms in protein translation.